The Mara-Serengeti Ecosystem and Greater Maasailand: Building the Role of Local Leaders, Institutions, and Communities - Reid, Robin S.; Kaelo D; Nkedianye DK; Kristjanson, Patricia M.; Said, Mohammed Yahya; Galvin, K.A.; Gambill I (Lincoln Institute of Land Policy, 2014)
Much of the effort to include communities in conservation of large landscapes has been driven by interests outside the savannas, either by national governments, NGOs, or foreign conservationists (Neumann 2002, Brockington et al. 2008). Once included in conservation planning only as an afterthought, local communities are now major stakeholders. However, initiatives driven, led, and managed by local leaders, communities, and institutions to meet the needs of both wildlife and people remain rare. The science of community- based conservation rarely answers the questions posed by local communities, integrates local knowledge, or builds the capacity of communities to do their own research. This chapter is the story of our efforts to turn community- based conservation around so that it is driven, led, and managed by local interests, needs, and people in Kenya’s northern Serengeti- Mara ecosystem, or the Mara.